PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 3 TAPUNG HILIR - Agus Hadi Muswanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The purpose of this study was to improve mathematics learning outcomes of Grade VII students of SMP Negeri 3 Tapung Hilir. The formulation of the problem is whether the application of the cooperative learning model type Numbered Head Together can improve mathematics learning outcomes of Grade VII students of SMP Negeri 3 Tapung Hilir? The hypothesis of this study is: if the cooperative learning model Numbered Head Together is applied, it can improve the mathematics learning outcomes of Grade VII students of SMP Negeri 3 Tapung Hilir. This research was carried out as much as III success. The percentage of teacher activity in the first cycle was 66.7% (category: good), in the second cycle was 83.3% (category: very good) and in the third cycle was 93.8% (category: very good). While the percentage of student learning activities in the first cycle was 51.4% (category: enough), in the second cycle was 64.9% (category: good) and in the third cycle was 83.9% (category: very good). Based on data analysis and research discussion. The mean student learning outcomes have increased. The mean student learning outcomes on the base score were 60.1, in the first cycle 69.2, in the second cycle 75.2 and in the third cycle 84.3. Based on the results of the research it can be concluded that the application of the Numbered Head Together cooperative learning model can improve mathematics learning outcomes of Grade VII students of SMP Negeri 3 Tapung Hilir